Paracetamol clinical dosing routine leads to paracetamol underexposure in an adult severely ill sub-Saharan African hospital population: a drug concentration measurement study - Jeannet C. Bos; Mabor C. Mistício; Ginto Nunguiane; Ron A. A. Mathôt; Reinier M. van Hest; Jan M. Prins (BMC Research Notes, 2017)
Abstract Background Hospitals in sub-Saharan Africa (SSA) continue to receive high numbers of severely ill (HIV-infected) patients with physical pain that may suffer from hepatic and renal dysfunction. Paracetamol is widely used for pain relief in this setting but it is unknown whether therapeutic drug concentrations are attained. The aim of this study was to assess the occurrence of therapeutic, sub-therapeutic and toxic paracetamol concentrations in SSA adult hospital population. Methods In a cross-sectional study, plasma paracetamol concentrations were measured in patients with an oral prescription in a referral hospital in Mozambique. From August to November 2015, a maximum of four blood samples were drawn on different time points for paracetamol concentration measurement and biochemical analysis. Study endpoints were the percentage of participants with therapeutic (≥ 10 and ≤ 20 mg/L), sub-therapeutic (< 10 mg/L) and toxic (> 75 mg/L) concentrations. Results Seventy-six patients with a median age of 37 years, a body mass index of 18.2, a haemoglobin concentration of 10.3 g/dL and an albumin of 29 g/L yielded 225 samples. 13.4% of participants had one or more therapeutic paracetamol concentrations. 86.6% had a sub-therapeutic concentration at all time points and 70.2% had two or more concentrations below the lower limit of quantification. No potentially toxic concentrations were found. Conclusions Routine oral dosing practices in a SSA hospital resulted in substantial underexposure to paracetamol. Palliation is likely to be sub-standard and oral palliative drug pharmacokinetics and dispensing procedures in this setting need further investigation.